Understanding and use of food labeling systems among Whites and Latinos in the United States and among Mexicans: Results from the International Food Policy Study, 2017 - Claudia Nieto; Alejandra Jáuregui; Alejandra Contreras-Manzano; Edna Arillo-Santillan; Simón Barquera; Christine M. White; David Hammond; James F. Thrasher (BMC, 2019)
Abstract Background Obesity and chronic diseases could be prevented through improved diet. Most governments require at least one type of food labeling system on packaged foods to communicate nutrition information and promote healthy eating. This study evaluated adult consumer understanding and use of nutrition labeling systems in the US and Mexico, the most obese countries in the world. Methods Adults from online consumer panels in the US (Whites n = 2959; Latinos n = 667) and in Mexico (n = 3533) were shown five food labeling systems: 1. Nutrition Facts Table (NFT) that shows nutrients of concern per serving; 2. Guideline Daily Amounts (GDA) that shows levels of nutrients of concern; 3. Multiple Traffic-Light (MTL) that color codes each GDA nutrient (green = healthy; yellow = moderately unhealthy; red = unhealthy); 4. Health Star Rating System (HSR) that rates foods on a single dimension of healthiness; 5. Warning Label (WL) with a stop sign for nutrients present in unhealthy levels. Participants rated each label on understanding ("easy"/"very easy to understand" vs "difficult"/"very difficult to understand"), and, for NFTs and GDAs, frequency of use ("sometimes"/"often" vs "never"). Mixed logistic models regressed understanding and frequency of use on indicators of labeling systems (NFT = ref), testing for interactions by ethnicity (US Latinos, US Whites, Mexicans), while controlling for sociodemographic and obesity-related factors. Results Compared to the NFT, participants reported greater understanding of the WL (OR = 4.8; 95% CI = 4.4-5.3) and lower understanding of the HSR (OR = 0.34, 95% CI = 0.31-0.37) and the MTL (OR = 0.56, 95% CI = 0.52-0.61), with similar patterns across ethnic subgroups. Participants used GDAs less often than NFTs (OR = 0.48; 95%CI = 0.41-0.55), with the greatest difference among US Whites (OR = 0.10; 95%CI = 0.07-0.14). Conclusions Understanding and use of the GDA was similar to that of the NFT. Whites, Latinos, and Mexicans consistently reported the best understanding for WLs, a FOPL that highlights unhealthfulness of a product. Therefore, a FOPL summary indicator, such as WLs, may be more effective in both the US and Mexico for guiding consumers towards informed food choices.